Implementation of Smart Branding Policy in the River City of Banjarmasin - Hamjen, Hilarion; Oktavianor, Tomi; Arbain, Taufik (Jurnal Bina Praja, 2023)
This study departs from the regulation of the Mayor of Banjarmasin Number 40 of 2019 concerning the Smart City Masterplan, which requires the implementation of Smart City Banjarmasin revised to maximize the identity of the river city as city branding, namely D(River) smart city. This study aims to identify policies and implementation of Smart Branding Policies in Banjarmasin. This study used a qualitative descriptive approach with data collection techniques carried out by triangulation of sources through literature studies, observation, in-depth interviews, and inductive data analysis. The results show that Smart Branding policies are contained in the Smart City Masterplan for 2022-2026, which was revised based on the 2021-2026 Medium Term Development Plan. Then the implementation of Smart Branding can be identified into three categories: Facilitation of ICT at Riverside View Tower, ICT System Integration in Tourist Areas, and Digitalization of Tourism and Cultural Promotion. In each category, there is a gap between implementation and ideal conditions due to a lack of public participation, data, resources, regulations, and disaster mitigation. However, it is recommended that the gap should be minimized by overcoming the identified constraints so that policy implementation becomes more optimal.